SUPERVISI PENDIDIKAN DALAM PERSPEKTIF TEORI DAN IMPLEMENTASI: TINJAUAN LITERATUR - Rahmi Malahayati; Defril Syafrin; Sufyarma Marsidin; Rifma; Tia Ayu Ningrum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze educational supervision from both theoretical and implementation perspectives through a literature review approach. The research employs a qualitative method using a literature review design, which involves examining various scholarly sources, including national and international journal articles, books, and relevant educational policy documents related to educational supervision. The findings indicate that educational supervision plays a strategic role in improving the quality of learning through continuous professional development of teachers, strengthening reflective practice, enhancing teacher performance, and fostering a collaborative school culture. Theoretically, supervision has evolved from an administrative-oriented approach to a more humanistic, collaborative, and reflective approach. However, in practice, several challenges are still identified, such as limited supervisor competence, teacher resistance, weak planning and follow-up of supervision, and the tendency of supervision to remain administrative in nature. On the other hand, the development of digital technology provides opportunities to develop more effective and adaptive supervision practices. Therefore, strengthening educational supervision through innovative, collaborative, and teacher-needs-based approaches is essential to sustainably improve the quality of learning.